If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22x = 25x + -6 Reorder the terms: 22x = -6 + 25x Solving 22x = -6 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 22x + -25x = -6 + 25x + -25x Combine like terms: 22x + -25x = -3x -3x = -6 + 25x + -25x Combine like terms: 25x + -25x = 0 -3x = -6 + 0 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| 6(2n-1)=2(5n-3)+4n | | 9y+1=8y-2 | | (u-7)(u+1)= | | 3(a-5)+7=-2 | | 3x^2-21x-36=0 | | -3(6-2t)=-48 | | 8z^2+20z-49=0 | | 5x+15-2x=25+3x-10 | | 5log(x+3)=12 | | 5x=42-3x | | x^2-6+3x^2-10x+2= | | 6x-1=-2(3-5x) | | 7=(t-1)-2(t-3) | | 9+3x=-(x+7) | | 16-x=4+5x | | h=-4t^2+4t+120 | | x^3+3x^2+2x=2x^2+4x | | 3(x-8)+15=-18 | | -1=-14+5x | | 10x-8=10x+5 | | b=zc+m | | 77r^2+53r-40=0 | | 4(x+5)=3(x-2)-2x+2 | | 42*84*3.14=x | | 3x^3-x^2-10x=-x^2+2 | | Y+9.4=10 | | 10x*4=80 | | 3x-15=120 | | 11-11x=-14-10x | | -a+8.5=14.2 | | -3(5+5m)=75 | | 1x+8=5 |